A Review of Pharmaceutical Recombinant Proteins and Gene Transformation Approaches in Transgenic Poultry - Sepideh Fallahi; Reza Mohammadhassan (Journal of Tropical Life Science, 2020)
Transgenic animals are employed to synthesize pharmaceutical recombinant proteins for three decades.Â There are many problems to use farm mammalian animals for recombinant production such as high cost of production and maintenance, long generation interval, toxic effects of some human-source pharmaceutical proteins in other mammalian and incompatibility of human-source glycosylation with the other mammalian' glycosylation that all lead to low efficiency. Thus, transgenic poultry has been considered as the bioreactor of recombinant protein production. Increasing demand for pharmaceutical human proteins caused to make considerable efforts to develop transgenic poultry producing eggs contain recombinant protein. In the present review, at the first, transgenic animal and poultry are compared for their benefits and limitations. Then, the protein content of the egg, the features, gene and promoter of the egg are studied. After that, the recent achievements of the producing pharmaceutical recombinant proteins are considered. In the following, there are some explanations about gene transformation approaches in poultry, including sperm-, testis-, PGCs, and blastocyst-mediated methods depending on CRISPR/Cas9, Retroviral vectors, and DNA microinjection techniques, and embryonic manipulation approaches such as windowing and Ex ovo for introducing and injecting transformed cells into eggs.